Characteristics of AISi10Mg Aluminum Alloy Plates Produced Through Additive Manufacturing Technique - Yaz, Mehmet; Ekinci, Omer; Balalan, Zulkuf; Özgün, Özgür (My University, 2025)
TThe microstructure and mechanical properties of AlSi10Mg aluminum alloy sheets produced by additive manufacturing method were revealed. It was clearly observed that the microstructure consisted of weld pools separated by boundaries. Furthermore, a small number of distributed pores with diameters ranging from 35 µm to 5 µm were detected in the microstructure. A few small-sized pores are a sign of good production. Vickers microhardness of the produced AlSi10Mg alloy was measured to be average 126.625 HV. Additionally, its tensile strength and three-point bending strength value were found to be 433 MPa and 548 MPa, respectively. The tensile fracture surface had many small and deep dimples while three-point bending fracture surface also possessed dimples, however, bigger and shallower compared with that of tensile fracture. Therefore, the tensile and three-point bending tests showed a reasonable ductile fracture behavior.
Keywords: Additive manufacturing; microhardness; microstructure; tensile strength; AlSi10Mg aluminum alloy; three-point bending strength